Interlibrary Loan and Cooperation Among Selected Academic Libraries in Kwara State, Nigeria: An Empirical Analysis. Issue 2 (6th March 2017) - Tella, Adeyinka; Sidiq, Aminat Omolola
ABSTRACT: This study examines interlibrary loan cooperation among six selected academic libraries in Kwara State, Nigeria. The study adopts a survey design with a sample size of one hundred (100) librarians and library officers selected from among academic libraries in Kwara State. Data were collected through a self-designed questionnaire and collected data were analyzed using frequency counts and percentages. The findings reveal that books and journals are the materials mostly available for interlibrary loan in all the participating academic libraries, and that the requesting and delivery methods used are emails, personal contact, Facebook and Twitter. The findings also show that inadequate funds, obsolescence of equipment for assessing digital information, and lack of documented policy on interlibrary loan are challenges facing the provision of interlibrary loans in academic libraries in the state. However, it is suggested that, if libraries begin to appreciate the usefulness of interlibrary loan services, then this will enable them to forge ahead toward satisfying their clienteles' information needs. To overcome the challenges facing interlibrary loan, it is recommended that proper planning, adequate funding, capacity building, and formulation of policy guiding interlibrary loan should be considered and instituted.